Perbandingan Dinamika Belajar Mahasiswa KIP-K dan Reguler : Tinjauan Kualitatif terhadap Motivasi dan Prestasi Belajar - Rio Pebrianto; Raden Roro Suci Nurdianti; Kurniawan Kurniawan (JURNAL ILMIAH NUSANTARA, 2025)
The study aims to explore in depth the dynamics of learning motivation and academic achievement between recipients of the KIP-K students and regular students in Economic Education Department of University Siliwangi. A qualitative case study approach was used, with data collected through in-depth interviews and documentation. The result show KIP-K students motivation is driven by external factors such a family economic conditions and parental expectations, whereas regular students are influenced by internal factors such as personal goals and career aspirations. Despite minor differences in academic performance, both groups demonstrate a relatively equal level of commitment and achievement. These findings provide important implications for educational institutions in designing more inclusive and responsive student development strategies.